Study of the spatial variability of moisture and compaction in soils with different plant covers (2016)
Soil is a dynamic system, with physical, chemical and biological properties that have high spatial variability, making necessary to use innovative methodologies to study this variability. The aim of this study was to determine the spatial variability of moisture and compaction in soils with different plant covers. The study was conducted in the department of Boyaca (Colombia), municipality of Sogamoso, Ombachita District. A total of 95 sampling points were measured as a rigid network in an area of 34.18 ha, which were georeferenced and aken as representative for the plant cover in the sampling area. The values of penetration resistance (PR) found in the soil ranged from 0.717 to 1.385 MPa, so that, as the depth increased, the PR increased, while the volumetric moisture presented an inversely proportional behavior for depth. The cover that prevailed in the study area was a mosaic of pastures and crops (MPC), at 30.1%. The moisture values were lower in the area planted with eucalyptus. The PR showed greater spatial dependence at a greater depth, while the moisture presented a moderate dependence at different depths.